An investigation of the operations of income generating projects on the performance of local authorities: a case study of Chipinge rural district council - Mushivazvo, Chamwazoda N. (Midlands State University, 2017)
The core principle behind this research was to carry out an “An investigation on the operations of Income generating projects on the overall performance of a Local Authority” A case study of Chipinge Rural District Council. Chipinge Rural council is local authority with the mandate of governing, administer the affairs and service delivery to the district populace. In line with the amendments made by central government to reduce grants to local authorities, the local authority then ventured in to Income generating projects so as to sustain service delivery and operations of the organisation at large. From the inception of the first project in 2009, right up to 2014, the operations of these projects were not reciprocating the efforts and funding invested in them. A review of relevant related literature was embarked on to come up with what authentic authors and scholars had to avail concerning the operations of Income generating projects of local authorities. The researcher depended heavily on scholarly journals for related literature review carried out. The research design adopted was descriptive which was used in conjunction with questionnaires and interviews to gather data. The data gathered was presented using tables and histograms, whereas analysis was improvised with the help of the measures of central tendency specifically the mode, which was facilitated by the Likert scale model. The researcher made recommendations conclusions based on the data gathered and analysed on how the operations of Income generating projects can amplified so as to trigger a positive performance on the overall performance of the local authority.